Conserving and managing mosaics in Libya (CaMMiL): the final project review1. (21st July 2015) - Wootton, William T.; El-Habashi, Alaa; Stewart, John D.; Walda, Hafed
Abstract: This is a review of a project aimed at assisting the Libyan Department of Archaeology with the conservation and management of their mosaic heritage. Over the course of a year we undertook an evaluation trip along the coast of Libya and then put on two workshops for the Department's staff to help build capacity. The workshops disseminated complementary content on the protection of mosaics and their management to two different contingents: managers and technicians. The teaching was intended to empower Libyans by giving them the confidence to make simple and sound decisions, and to encourage them to join more formal training courses run by major international organisations. The project was a collaboration with the Department and was supported by the Getty Foundation, King's College London and the Society for Libyan Studies. Abstract : هذه مراجعة لمشروع يهدف إلى مساعدة دائرة الآثار الليبية في الحفاظ على وإدارة تراث الفسيفساء الخاص بهم . لقد قمنا وعلى مدار عام برحلة تقييمية على طول ساحل ليبيا ومن ثم وضعنا ورشتي عمل للعاملين في الدائرة للمساعدة على بناء القدرة لديهم . وزّعت ورشتا العمل مضمون تكميلي حول الحفاظ على الفسيفساء وإدارته وذلك على فريقين مختلفين : المدراء والتقنيّون . لقد هدف التدريس إلى تمكين الليبين وذلك من خلال منحهم الثقة لإتخاذ قرارات بسيطة وسليمة، وتشجيعهم على الإنضمام إلى دورات تدريبية أكثر رسمية تُدار من قِبل منظمات دولية رئيسية. لقد كان المشروع بالتعاون مع الدائرة وكان بدعم من مؤسسة "جيتي " وكلّية "كنجز" لندن وجمعية الدراسات الليبية.